Temporal and spatial overlap in the behaviors of a native and invasive tree squirrel in southern California. Issue 2 (4th March 2022) - Ortiz, Janel L.
Abstract : The native western gray squirrel ( Sciurus griseus ) and introduced fox squirrel ( Sciurus niger ) can be found occupying various locales in southern California (USA) either coexisting or living separately. Since the introduction of the fox squirrel in 1904, there have been local extinctions of gray squirrels in parks and natural areas in urban and suburban locations. Little research has focused on the coexistence of these two species with no work with an in-depth focus on their behavior. The objective of this study was to observe the daily activity of gray and fox squirrels in areas where they coexist and those they occupy alone to determine if the presence of the fox squirrel is negatively impacting the behavior of the gray squirrel. Focal animal observations were conducted using the instantaneous sampling method in three habitat types: coexistence, gray squirrel only, and fox squirrel only. Daily activity related to self-maintenance, communication, feeding, and the location in which the animals were observed were recorded within 15-min observations of individual squirrels. There was no negative impact from the fox squirrels; however, there were behavioral similarities among the species when coexisting which suggests niche overlap. An overlap in the use of space and time in shared habitats can be detrimental to the already declining population of gray squirrels in urban and suburban habitats, particularly in times when environmental conditions are less than ideal and resources are less abundant.